Predictors of sudden cardiac death and the impact of coronary artery bypass grafting on their development - Rasulov , Alisher; Kurbanov , Ravshanbek; Mullabaeva , Guzal; Tursunov, Ergashali; Kevorkov, Amayak; Sayfiddin Hoji, Qadriddin (CARDIOLOGY OF UZBEKISTAN, 2025)
Sudden Cardiac Death (SCD) is one of the most severe and life-threatening manifestations of cardiovascular diseases and is among the leading causes of mortality worldwide. The primary pathogenic factors contributing to the development of this condition include ischemic heart disease (IHD), ventricular arrhythmias, reduced left ventricular ejection fraction (LVEF), and the formation of scar tissue in the myocardium.The mechanism underlying SCD is complex, involving a combination of myocardial ischemia, electrical instability, and morphological changes, all of which contribute to the onset of malignant arrhythmias.Coronary artery bypass grafting (CABG) is an effective revascularization technique in patients with ischemic heart disease. It not only alleviates symptoms but also significantly improves long-term prognosis by enhancing cardiac function.Studies have shown that CABG, particularly in patients with reduced LVEF, decreases overall mortality and the risk of developing SCD.In conclusion, CABG plays an important role in the prevention of SCD, but it is not a standalone solution. A thorough analysis of the underlying risk factors, early identification of high-risk patients, and the development of individualized, comprehensive preventive and therapeutic strategies represent the most effective approach in reducing SCD incidence.